Mrs. Lizzy is dizzy! - Gutman, Dan; Paillot, Jim (New York : Harper, 2010)
Ella Mentry School's newest teacher, Mrs. Lizzy, has some very strange ideas about learning during recess.
M
610
M
Keywords: Schools -- Fiction; Teachers -- Fiction; Recess -- Fiction; Humorous stories